A high-performance free-standing Zn anode for flexible zinc-ion batteries. Issue 22 (31st May 2021) - Gao, Chenxi; Wang, Jiawei; Huang, Yuan; Li, Zixuan; Zhang, Jiyan; Kuang, Haoze; Chen, Shuhao; Nie, Zanxiang; Huang, Shuyi; Li, Wei; Li, Yubo; Jin, Shunyu; et al.
Abstract : A highly flexible free-standing Zn anode for ZIBs is fabricated from commercial Zn paste, carbon nanotubes, and poly(vinylidene fluoride)- co -hexafluoropropylene via spin coating. ZIBs with free-standing Zn anode showed improved rate performances. Abstract : Zinc-ion batteries (ZIBs) have attracted significant attention owing to their high safety, high energy density, and low cost. ZIBs have been studied as a potential energy device for portable and flexible electronics. Here, a highly flexible free-standing Zn anode is fabricated using a simple spin-coating technique, and its application in ZIBs is demonstrated. The free-standing Zn anode precursor is formed by mixing Zn particles with carbon nanotubes and poly(vinylidene fluoride)- co -hexafluoropropylene (PVDF-HFP). The hexafluoropropylene group in PVDF-HFP improves the mechanical properties of the free-standing Zn anode, whereas the carbon nanotubes created percolation conduction in the composite electrode, leading to an increased electrical conductivity of the anode. Owing to the excellent electrical conductivity and high specific surface area of the free-standing Zn anode, ZIBs with high capacity, rate performance, and mechanical flexibility are achieved. The volumetric energy density of the ZIBs reaches 8.22 mW h cm −3 with a battery thickness of 0.4 mm. This work demonstrates that free-standing Zn anodes are promising anodes for flexible ZIBs.